Internet Addiction and Personality: Association with Impulsive Sensation Seeking and Neuroticism-Anxiety Traits - Othman, Zahiruddin; Chung, Wah Lee; Yee, Cheng Kueh (Japan International Cultural Exchange Foundation, 2017)
Introduction: The internet has revolutionized the information age. There has been growing concern regarding internet addiction, despite its benefits. Personality trait such as neuroticism has been linked with internet addiction. Objective: The aim of the present study was to determine the prevalence of internet addiction and its association with personality traits among college students. Methods: College students age 18-24 who were doing an attachment in a government hospital were recruited into the study. Internet addiction was assessed using the internet addiction test (IAT), whilst personality traits by using the cross cultural Malay language 40-item Zuckerman-Kuhlman personality questionnaire (ZKPQ-M-40-CC) Results: The prevalence of internet addiction was 31.8%, with moderate and severe use of internet at 30.7% and 1.1%, respectively. Based on multiple logistic regression analysis, the impulsive sensation seeking and neuroticism-anxiety traits were found to be significantly associated with internet addiction. Conclusions: The prevalence of internet addiction is comparable to other studies conducted in Malaysia. Personality traits impulsive sensation seeking and neuroticism-anxiety emerged as significant associated factors with internet addiction. Further study to understand the role of personality traits in the development of internet addiction is recommended.